2006
DOI: 10.1080/14660820510043235
|View full text |Cite
|
Sign up to set email alerts
|

Management of respiration in MND/ALS patients: An evidence based review

Abstract: This systematic review comprises an objective appraisal of the evidence in regard to the management of respiration in patients with motor neuron disease (MND/ALS). Studies were identified through computerised searches of 32 databases. Internet searches of websites of drug companies and MND/ALS research web sites, 'snow balling' and hand searches were also employed to locate any unpublished study or other 'grey literature' on respiration and MND/ALS. Since management of MND/ALS involves a number of health profe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
9

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 78 publications
0
37
0
9
Order By: Relevance
“…The decision was made because they wished to survive as long as possible and there would be a need for an intervention at some point along the disease's trajectory (Table 2: Non-acceptance: Some participants were forthright about their fear of the future. They were more focused on living in the present and only confronted issues when there was an obvious need ( Table 2: 12). This meant that the ability to make a decision based on what could occur in the future was curtailed; they were in a state of active denial or nonacceptance (Table 2: 13).…”
Section: Acceptance and Needmentioning
confidence: 99%
See 1 more Smart Citation
“…The decision was made because they wished to survive as long as possible and there would be a need for an intervention at some point along the disease's trajectory (Table 2: Non-acceptance: Some participants were forthright about their fear of the future. They were more focused on living in the present and only confronted issues when there was an obvious need ( Table 2: 12). This meant that the ability to make a decision based on what could occur in the future was curtailed; they were in a state of active denial or nonacceptance (Table 2: 13).…”
Section: Acceptance and Needmentioning
confidence: 99%
“…While rates of acceptance of gastrostomy are not available for the UK, rates in the USA range from 0-63% [9]. Evidence-based guidelines based largely on expert opinion recommend the use of NIV in ALS [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…HMV 적용 환자의 실태 [4], 관련장비의 효용성 [8], 건강상태에 대한 영향요인과 다학제 접근의 효과 [10][11][12][13][14], HMV 적용 환자 에 관한 체계적 고찰과 가이드라인 제시 [15][16][17] 등 다양한 형태 로 많은 연구들이 보고되고 있다. 그러나 국내에서는 HMV 적 용 환자와 관련한 실태조사 [6,18], 삶의 질과 재입원의 영향요 인 [7,19] Table 1).…”
Section: 그동안 Hmv 적용 환자와 관련된 국외 연구를 살펴보면unclassified
“…6,7 Patients with ALS usually die from hypoventilation, 8 with hypoxemia and hypercapnia often precipitated by respiratory infections, aspiration pneumonia, or bronchial impaction. 9 The first study of NIV in ALS reported that continuous daily use delayed or even eliminated the need for a tracheostomy. 10 Two years later, Pinto et al 11 published a prospective controlled trial with ALS subjects with respiratory failure and demonstrated that total survival and survival from respiratory symptom onset were better in subjects with ALS receiving NIV compared with palliative care.…”
Section: When To Start Niv?mentioning
confidence: 99%